Strategic planning decisions in the high tech industry - Daim, Tugrul; Beyhan, Berna; Basoglu, Nuri (Springer London Imprint: Springer, 2013)
The scale and complexity of research and practices of open innovation mandate a correspondingly sophisticated form of decision making. Strategic Planning Decisions brings together a number of tools that ease the decision process in technology companies, providing both conceptual frameworks and practical applications. Innovative approaches are presented such as an ontology-based model where all the relevant aspects of a potential technology are interrelated to provide a comprehensive and logically connected data pool for decision makers. Divided into two sections, Strategic Planning Decisions describe both strategic approaches using the decision tools, and tactical approaches. Some of these tools are expanded while some others are embedded in a model that will lay the ground for practical application. These include: ·         bibliometric analysis, ·         ontology, ·         roadmapping, ·         lead user, six sigma, and ·         multi-actor & multi-objective decision making methods Recent research and relevant theory  are balanced with up-to-date practical applications and hands-on techniques making Strategic Planning Decisions ideal for engineers who wish to keep up-to-date with current ideas in the field of TM. It also provides workable methods for practising managers from all levels who wish to apply a more rigorous approach in their work and consultants concerned with technology assessment and its management.